CONSEQUENCES OF INCREASING THE MINIMUM WAGE IN UKRAINE TWICE - Boreiko V.І. (The actual problems of regional economy development, 2017)
In the article the views of scientists on the role of incomes of the poorest people in providing of economic development of the country and consequences of increasing the minimum wage in Ukraine twice are investigated; the dynamics of change in Ukraine minimum wage during a decade are analyzed and decline in living standards of population during this period is shown; measures, which should be taken for non-inflationary growth in incomes of the population, are grounded; it is disclosed that such measures should include unification of income tax for individuals and single social contribution and restoration of a progressive taxation of incomes of the working population.